Method for detecting hydrogen sulfide
By using Fe3O4, α-Fe2O3 and γ-Fe2O3 prepared in specific preparation methods as sensitive materials, catalyzed luminescence detection of hydrogen sulfide, solving the problems of low sensitivity and poor specificity in the detection of hydrogen sulfide in the prior art, and achieving high efficiency and selection The detection effect of good hydrogen sulfide.
Patent Information
- Application Number
- CN202411650126.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The prior art is difficult to efficiently and selectively detect hydrogen sulfide gas, and there are problems such as low sensitivity, poor specificity, slow speed, poor reproducibility and poor stability.
Fe3O4, α-Fe2O3 and γ-Fe2O3 prepared using specific preparation methods are used as sensitive materials to detect hydrogen sulfide by catalytic luminescence, and the unique microstructure of these materials is used to improve the sensitivity and specificity of the detection.
It realizes hydrogen sulfide detection with high sensitivity, good specificity, fast speed, good reproducibility, good stability and high accuracy, and can specifically measure hydrogen sulfide without being disturbed by other substances.
Smart Images

Figure CN119438186A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of detection technology, and in particular to a method for detecting hydrogen sulfide. Background Art
[0002] Hydrogen sulfide (H2S) is a colorless, acidic, highly toxic gas with a foul odor like rotten eggs. It is a toxic substance widely present in industrial raw gas, such as natural gas, coke oven gas and liquefied petroleum gas. Hydrogen sulfide is both a nerve agent and a suffocating and irritating gas, which mainly damages the central nervous system and respiratory system, eyes and heart, etc.; mild cases show irritation symptoms such as tearing, eye stinging, runny nose and burning sensation in the throat, or accompanied by headache, dizziness, fatigue, nausea, etc.; moderate poisoning patients have aggravated mucosal irritation symptoms, cough, chest tightness, blurred vision, conjunctival edema, obvious headache, dizziness and other symptoms, and mild consciousness disorder; severe poisoning will cause coma, pulmonary edema, respiratory and circulatory failure. Low concentrations of H2S gas leakage will pose a huge risk to the environment and physical health. Therefore, it is of great significance to realize convenient and selective detection of H2S gas for environmental hygiene and life safety.
[0003] In view of this, this invention is proposed. Summary of the invention
[0004] The purpose of the present invention is to provide a method for detecting hydrogen sulfide with high sensitivity, good specificity, fast speed, good reproducibility, good stability and high accuracy.
[0005] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0006] The present invention provides a method for detecting hydrogen sulfide, comprising the following steps:
[0007] The hydrogen sulfide gas reacts under the catalysis of the sensitive material, and the luminescent signal of the gas after the reaction is detected; the sensitive material includes at least one of Fe3O4, α-Fe2O3 and γ-Fe2O3;
[0008] The preparation method of Fe3O4 comprises: reacting FeCl3·6H2O aqueous solution, FeCl2·4H2O aqueous solution and ammonia aqueous solution for 25 to 35 minutes, and then separating, washing and drying in sequence to obtain Fe3O4;
[0009] The preparation method of α-Fe2O3 comprises: calcining the Fe3O4 at 300±5°C for 2.8 to 3.2 hours to obtain the α-Fe2O3;
[0010] The preparation method of the γ-Fe2O3 comprises: calcining the Fe3O4 at 500±5°C for 2.8 to 3.2 hours to obtain the γ-Fe2O3.
[0011] Furthermore, the molar ratio of FeCl3·6H2O in the FeCl3·6H2O aqueous solution to FeCl2·4H2O in the FeCl2·4H2O aqueous solution is 1:(0.45-0.55).
[0012] Furthermore, the mass ratio of FeCl3·6H2O in the FeCl3·6H2O aqueous solution to NH3 in the ammonia aqueous solution is 10:(0.2-1).
[0013] Furthermore, the concentration of the FeCl3·6H2O aqueous solution is 0.08-0.12 mol / L.
[0014] Furthermore, the concentration of the FeCl2·4H2O aqueous solution is 0.045-0.055 mol / L.
[0015] Furthermore, the concentration of the ammonia solution is 4wt% to 6wt%.
[0016] Further, it includes at least one of the following features (1) to (3);
[0017] (1) The separation comprises magnetic decantation separation;
[0018] (2) The washing comprises: washing with ethanol and deionized water;
[0019] (3) The drying comprises: drying at 55 to 65° C. for 10 to 15 hours.
[0020] Furthermore, the detection wavelength of the luminescent signal is 300-555 nm.
[0021] Furthermore, the reaction temperature is 180-300°C.
[0022] Furthermore, the carrier gas includes air, and the flow rate of the carrier is 500 to 950 mL / min.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention adopts Fe3O4, α-Fe2O3 and γ-Fe2O3 prepared by a specific preparation method as sensitive materials, and catalytic luminescence is used to detect hydrogen sulfide, which has the advantages of high sensitivity, good specificity, fast speed, good reproducibility, good stability, accuracy, etc., and can specifically measure hydrogen sulfide without interference from other substances. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 The XRD spectra of Fe3O4 prepared in Example 1, γ-Fe2O3 prepared in Example 2, and α-Fe2O3 prepared in Example 3 of the present invention are shown.
[0027] Figure 2 TEM images of γ-Fe2O3 prepared in Example 2 of the present invention, α-Fe2O3 prepared in Example 3, and Fe3O4 prepared in Example 1.
[0028] Figure 3 It is the response signal of hydrogen sulfide on the surface of different materials in the present invention.
[0029] Figure 4 These are the response signals of different gases on the surfaces of γ-Fe2O3 prepared in Example 2, α-Fe2O3 prepared in Example 3, and Fe3O4 prepared in Example 1 of the present invention.
[0030] Figure 5 It is the response intensity of hydrogen sulfide, carbon disulfide, isobutyraldehyde and ammonium sulfide on the surface of commercial γ-Fe2O3 of the present invention.
[0031] Figure 6 The response curve of γ-Fe2O3 prepared in Example 2 of the present invention to different concentrations of hydrogen sulfide.
[0032] Figure 7 This is the response curve of α-Fe2O3 prepared in Example 3 of the present invention to different concentrations of hydrogen sulfide.
[0033] Figure 8 The following is the response curve of Fe3O4 prepared in Example 1 of the present invention to different concentrations of hydrogen sulfide.
[0034] Fig. 9 The reproducibility of detecting hydrogen sulfide using the γ-Fe2O3 prepared in Example 2 of the present invention.
[0035] Fig.10 The reproducibility of hydrogen sulfide detection of α-Fe2O3 prepared in Example 3 of the present invention.
[0036] Fig.11 The reproducibility of detecting hydrogen sulfide using Fe3O4 prepared in Example 1 of the present invention.
[0037] Fig.12The stability of hydrogen sulfide was tested for the γ-Fe2O3 prepared in Example 2 of the present invention, the α-Fe2O3 prepared in Example 3, and the Fe3O4 prepared in Example 1.
[0038] Fig.13 This is a relationship diagram between the detection signal of hydrogen sulfide detected by γ-Fe2O3 prepared in Example 2 of the present invention and the hydrogen sulfide concentration.
[0039] Fig.14 This is a relationship diagram between the detection signal of hydrogen sulfide detected by α-Fe2O3 prepared in Example 3 of the present invention and the hydrogen sulfide concentration.
[0040] Fig.15 This is a relationship diagram between the detection signal of hydrogen sulfide detected by Fe3O4 prepared in Example 1 of the present invention and the hydrogen sulfide concentration. DETAILED DESCRIPTION
[0041] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0042] A method for detecting hydrogen sulfide of the present invention is described in detail below.
[0043] In some embodiments of the present invention, a method for detecting hydrogen sulfide is provided, comprising the following steps:
[0044] The hydrogen sulfide gas reacts under the catalysis of the sensitive material, and the luminescent signal of the gas after the reaction is detected; the sensitive material includes at least one of Fe3O4, α-Fe2O3 and γ-Fe2O3;
[0045] The preparation method of Fe3O4 comprises: reacting FeCl3·6H2O aqueous solution, FeCl2·4H2O aqueous solution and ammonia aqueous solution for 25 to 35 minutes, and then separating, washing and drying in sequence to obtain Fe3O4;
[0046] The preparation method of α-Fe2O3 comprises: calcining the above Fe3O4 at 300±5°C for 2.8-3.2h to obtain α-Fe2O3;
[0047] The preparation method of γ-Fe2O3 comprises: calcining the above Fe3O4 at 500±5°C for 2.8-3.2h to obtain γ-Fe2O3.
[0048] The preparation method of the catalyst has an important influence on the catalyst's crystal form, particle size, specific surface area, exposed crystal surface and other microstructures. Therefore, for the same catalyst, the difference in preparation method will have an important impact on its performance.
[0049] The present invention adopts Fe3O4, α-Fe2O3 and γ-Fe2O3 prepared by a specific preparation method as sensitive materials for catalytic luminescence detection of hydrogen sulfide, which has the advantages of high sensitivity, good specificity, fast speed, good reproducibility, good stability, accuracy, etc., and can specifically measure hydrogen sulfide without being interfered by other substances; while the existing commercial Fe3O4, α-Fe2O3 and γ-Fe2O3 also respond to other gases besides hydrogen sulfide, and have poor specificity.
[0050] In some embodiments of the present invention, the temperature for the reaction of the FeCl3·6H2O aqueous solution, the FeCl2·4H2O aqueous solution and the ammonia aqueous solution is room temperature; preferably 15 to 30°C.
[0051] In some embodiments of the present invention, the molar ratio of FeCl3·6H2O in the FeCl3·6H2O aqueous solution to FeCl2·4H2O in the FeCl2·4H2O aqueous solution is 1:(0.45-0.55).
[0052] In some embodiments of the present invention, the mass ratio of FeCl3·6H2O in the FeCl3·6H2O aqueous solution to NH3 in the ammonia aqueous solution is 10:(0.2-1).
[0053] In some embodiments of the present invention, the volume ratio of the FeCl3·6H2O aqueous solution to the ammonia aqueous solution is 100:(1-5).
[0054] In some embodiments of the present invention, the concentration of the FeCl3·6H2O aqueous solution is 0.08 to 0.12 mol / L.
[0055] In some embodiments of the present invention, the concentration of the FeCl2·4H2O aqueous solution is 0.045 to 0.055 mol / L.
[0056] In some embodiments of the present invention, the concentration of the aqueous ammonia solution is 4 wt % to 6 wt %.
[0057] In some embodiments of the invention, the separating comprises separation by magnetic decantation.
[0058] In some embodiments of the present invention, washing comprises: washing with ethanol and deionized water;
[0059] In some embodiments of the present invention, drying comprises: drying at 55-65° C. for 10-15 hours.
[0060] In some specific embodiments of the present invention, the preparation method of Fe3O4 comprises the following steps:
[0061] The FeCl3·6H2O aqueous solution and the FeCl2·4H2O aqueous solution were mixed, and then the ammonia aqueous solution was slowly added dropwise under mechanical stirring, and after reacting at room temperature for 30 minutes, the crude product was separated by magnetic decantation;
[0062] The crude product was washed with anhydrous ethanol and deoxygenated deionized water for multiple times, and then dried in a vacuum drying oven at 60° C. for 12 h to obtain Fe3O4.
[0063] In some specific embodiments of the present invention, the preparation method of α-Fe2O3 comprises the following steps:
[0064] The Fe3O4 prepared by the above-mentioned Fe3O4 preparation method is calcined at 300°C for 3h to obtain α-Fe2O3.
[0065] In some specific embodiments of the present invention, the preparation method of γ-Fe2O3 comprises the following steps:
[0066] The Fe3O4 prepared by the above-mentioned Fe3O4 preparation method is calcined at 500°C for 3 hours to obtain γ-Fe2O3.
[0067] In some embodiments of the present invention, the detection wavelength of the luminescent signal is 300-555nm; typically but not limitatively, for example, the detection wavelength of the luminescent signal can be 300nm, 320nm, 350nm, 380nm, 410nm, 450nm, 500nm, 555nm or a range of any two thereof; preferably, the detection wavelength of the luminescent signal is 350nm.
[0068] In some embodiments of the present invention, the reaction temperature is 180-300°C; typically but not limiting, for example, the reaction temperature can be 180°C, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C or a range of any two thereof; preferably, the reaction temperature is 210°C.
[0069] In some embodiments of the present invention, the carrier gas includes air, and the flow rate of the carrier is 500-950 mL / min; typically but not limitatively, for example, the flow rate of the carrier can be 500 mL / min, 600 mL / min, 700 mL / min, 800 mL / min, 900 mL / min, 950 mL / min or a range of any two thereof; preferably, the flow rate of the carrier is 900 mL / min.
[0070] In some embodiments of the present invention, the method for detecting hydrogen sulfide specifically comprises the following steps:
[0071] The hydrogen sulfide gas enters the detection device and is heated to the reaction temperature. The hydrogen sulfide gas contacts the sensitive material. On the surface of the sensitive material, the hydrogen sulfide gas is oxidized by the oxygen in the air to generate a catalytic luminescence signal, and the generated luminescence signal is detected.
[0072] In some embodiments of the present invention, the detection device includes: an automatic sampling unit, a catalytic luminescence reactor and a detection instrument;
[0073] Among them, the automatic sampling unit can pass high-concentration hydrogen sulfide gas into the gas mixer, use air as the diluent gas, dilute it into the target concentration of hydrogen sulfide gas, and then inject it through the six-way valve to complete the fully automatic cyclic quantitative timing injection;
[0074] The catalytic luminescence reactor comprises a reaction chamber, which comprises an air inlet, an air outlet and a substrate; the reaction chamber comprises a quartz tube, the substrate comprises a ceramic rod, a catalytic layer is attached to the surface of the ceramic rod, the material of the catalytic layer comprises the above-mentioned sensitive material, and the thickness of the catalytic layer is 2 to 5 mm; the hydrogen sulfide gas flow enters from the air inlet of the reaction chamber, reacts with the catalytic layer, and then flows out from the air outlet of the reaction chamber;
[0075] The detection instrument includes a weak luminescence measuring instrument host (BPCL-1-TGC), a detector and a controller, which can accurately detect the light signal generated by hydrogen sulfide during catalytic luminescence.
[0076] Example 1
[0077] The preparation method of Fe3O4 provided in this embodiment comprises the following steps:
[0078] Dissolve 2.703 g of FeCl3·6H2O in 100 mL of deionized water to obtain a FeCl3·6H2O aqueous solution; dissolve 0.9942 g of FeCl2·4H2O in 100 mL of deionized water to obtain a FeCl2·4H2O aqueous solution;
[0079] The FeCl3·6H2O aqueous solution and the FeCl2·4H2O aqueous solution were transferred to a three-necked flask, and 1-5 mL of 5 wt% ammonia aqueous solution was slowly added dropwise under mechanical stirring at room temperature, and stirring was continued for 30 min. The crude product was separated by magnetic decantation to obtain a crude product; the crude product was washed with anhydrous ethanol and deoxygenated deionized water for multiple times, and then dried in a vacuum drying oven at 60°C for 12 h to obtain Fe3O4.
[0080] Example 2
[0081] The preparation method of γ-Fe2O3 provided in this embodiment comprises the following steps:
[0082] The Fe3O4 prepared in Example 1 was calcined in a muffle furnace at 300°C for 3 hours to obtain γ-Fe2O3.
[0083] Example 3
[0084] The preparation method of γ-Fe2O3 provided in this embodiment comprises the following steps:
[0085] The Fe3O4 prepared in Example 1 was calcined in a muffle furnace at 500°C for 3 hours to obtain α-Fe2O3.
[0086] Test Example 1
[0087] XRD tests were performed on Fe3O4 obtained in Example 1, γ-Fe2O3 obtained in Example 2, and α-Fe2O3 obtained in Example 3. The results are as follows: Figure 1 shown.
[0088] from Figure 1 It can be seen that the Fe3O4 prepared in Example 1 is a cubic phase, and its PDF standard card number is 88-0315; the γ-Fe2O3 prepared in Example 2 is a cubic phase, and its PDF standard card number is 39-1346; and the α-Fe2O3 prepared in Example 3 is a hexagonal phase, and its PDF standard card number is 33-0664.
[0089] TEM tests were performed on the γ-Fe2O3 prepared in Example 2, the α-Fe2O3 prepared in Example 3, and the Fe3O4 prepared in Example 1. The results are as follows: Figure 2 As shown. Among them, Figure 2 (a) is γ-Fe2O3 obtained in Example 2, Figure 2 (b) is α-Fe2O3 obtained in Example 3, Figure 2 (c) is Fe3O4 obtained in Example 1.
[0090] from Figure 2It can be seen that the average particle size of Fe3O4 prepared in Example 1 is 263nm; the average particle size of γ-Fe2O3 prepared in Example 2 is 15nm; and the average particle size of α-Fe2O3 prepared in Example 3 is 20nm.
[0091] Test Example 2
[0092] Detection device: including: automatic sampling unit, catalytic luminescence reactor and detection instrument;
[0093] Among them, the automatic sampling unit passes high-concentration hydrogen sulfide gas into the gas mixer, uses air as the diluent gas to dilute it into the target concentration of hydrogen sulfide gas, and then injects it through the six-way valve to complete the fully automatic cyclic quantitative timing injection;
[0094] The catalytic luminescence reactor comprises a quartz tube, the quartz tube comprises an air inlet, an air outlet and a ceramic rod, a catalytic layer is attached to the surface of the ceramic rod, the material of the catalytic layer comprises a sensitive material, and the thickness of the catalytic layer is 2 to 5 mm;
[0095] The detection instrument includes a weak luminescence measuring instrument host (BPCL-1-TGC), a detector and a controller, which can accurately detect the light signal generated by hydrogen sulfide during catalytic luminescence.
[0096] Detection steps: The gas to be tested enters the catalytic luminescence reactor through the automatic sampling unit and is heated to the reaction temperature. The gas to be tested contacts the sensitive material of the catalytic layer. On the surface of the sensitive material, the gas to be tested is oxidized by oxygen in the air to generate a catalytic luminescence signal, which is then detected by a detection instrument.
[0097] Detection conditions: detection wavelength is 350nm, reaction temperature is 210℃, carrier gas is air, and carrier gas flow rate is 900mL / min.
[0098] The following tests were all performed using the above-mentioned testing device, testing steps and testing conditions.
[0099] The γ-Fe2O3 prepared in Example 2, the α-Fe2O3 prepared in Example 3, the Fe3O4 prepared in Example 1, ZnO, SiO2, DyO and Y2O3 were used as sensitive materials to detect hydrogen sulfide gas with a concentration of 200 ppm. The results are as follows: Figure 3 shown.
[0100] from Figure 3 It can be seen that when γ-Fe2O3 detects hydrogen sulfide, the luminescence signal is the strongest, and the signals of α-Fe2O3, Fe3O4, ZnO, SiO2, DyO and Y2O3 decrease in turn.
[0101] The γ-Fe2O3 prepared in Example 2, the α-Fe2O3 prepared in Example 3, and the Fe3O4 prepared in Example 1 were respectively used to detect hydrogen sulfide gas with a concentration of 200 ppm and the following substances with a concentration of 20000 ppm: ethanol, n-propanol, n-butanol, acetic acid, 2-heptanone, cycloheptanone, acetophenone, n-propanal, formaldehyde, phenylacetaldehyde, isobutyraldehyde, n-butyraldehyde, acetone aldehyde, acetaldehyde, acrolein, benzene, o-xylene, ethylbenzene, isopropylbenzene, trimethylamine, ethanethiol, dimethyl sulfide, styrene, ammonia water, ammonium sulfide solution, petroleum ether, carbon disulfide, trichloroethylene, 1,2-dichloroethane, dimethylamine, diethylamine, cyclopropylcarbinol, and methanol.
[0102] from Figure 4 It can be seen that the γ-Fe2O3 prepared in Example 2, the α-Fe2O3 prepared in Example 3 and the Fe3O4 prepared in Example 1 all respond only to hydrogen sulfide and have no response to other gases, and have excellent specificity.
[0103] Commercialized γ-Fe2O3 purchased from Bohuasi Nanotechnology (Ningbo) Co., Ltd. was used to detect 200 ppm of hydrogen sulfide gas and 20,000 ppm of other gases, including carbon disulfide, isobutyl alcohol and ammonium sulfide. The results are as follows: Figure 5 shown.
[0104] from Figure 5 It can be seen that the response intensity of hydrogen sulfide on the commercial γ-Fe2O3 surface is lower than that on the γ-Fe2O3 surface prepared in Example 2, and the specificity of the commercial γ-Fe2O3 is poor, and carbon disulfide, isobutyraldehyde, and ammonium sulfide all produce responses; thus, it is shown that the material prepared by the preparation method of the present invention has excellent sensitivity and specific response to hydrogen sulfide.
[0105] The γ-Fe2O3 prepared in Example 2, the α-Fe2O3 prepared in Example 3 and the Fe3O4 prepared in Example 1 were used to detect hydrogen sulfide gas with concentrations of 125ppm, 200ppm and 303ppm, and the response time and recovery time of the kinetic response curve were recorded. The results were Figure 6 , Figure 7 and Figure 8 As shown. Among them, Figure 6 , Figure 7 and Figure 8 In the figure, 1 is hydrogen sulfide gas with a concentration of 300 ppm, 2 is hydrogen sulfide gas with a concentration of 200 ppm, and 3 is hydrogen sulfide gas with a concentration of 125 ppm.
[0106] from Figure 6 to Figure 8It can be seen that the material prepared in the present invention starts to be sampled from the 20th second, reaches the response peak at 22 seconds, and drops to the baseline at 22.5 seconds, so the response time is 2 seconds, and the recovery time is 0.5 seconds. The prepared material has a rapid detection capability.
[0107] The γ-Fe2O3 prepared in Example 2, the α-Fe2O3 prepared in Example 3 and the Fe3O4 prepared in Example 1 were used to detect hydrogen sulfide gas with a concentration of 200 ppm. The detection was repeated ten times, and the automatic sampling was repeated ten times. The parallel determination was performed, and the sampling time and sampling interval were both 20 seconds. The results are shown in FIG. Fig. 9 , Fig.10 and Fig.11 shown.
[0108] from Figures 9 to 11 It can be seen that the mean values of the luminescence intensity are 7060.6, 3970.4 and 1468.1, respectively, and the relative standard deviations are 1.48%, 2.87% and 4.06%, respectively. The obtained signals can remain stable and have excellent repeatability.
[0109] The γ-Fe2O3 prepared in Example 2, the α-Fe2O3 prepared in Example 3 and the Fe3O4 prepared in Example 1 were used to detect the hydrogen sulfide gas with a concentration of 200 ppm. The luminescent signal was detected repeatedly for 14 days. The results are as follows: Fig.12 shown.
[0110] from Fig.12 It can be seen that the standard deviations of hydrogen sulfide measured repeatedly for 14 days for the three materials are 1.4%, 2.2% and 3.3%, respectively, with good stability.
[0111] The γ-Fe2O3 prepared in Example 2, the α-Fe2O3 prepared in Example 3 and the Fe3O4 prepared in Example 1 were used to detect hydrogen sulfide gas with concentrations of 25ppm, 50ppm, 66.67ppm, 100ppm, 125ppm, 166.7ppm, 200ppm, 250ppm, 303ppm, 333ppm, 416.6ppm, 500ppm, 625ppm, 714ppm, 833ppm, 909ppm and 1000ppm, respectively, and the measured catalytic luminescence signals were subjected to linear regression to obtain a standard curve. The results are shown in FIG. Fig.13 , Fig.14 and Fig.15 shown.
[0112] from Fig.13 It can be seen that the regression equation corresponding to γ-Fe2O3 is: S = 0.23C 2 -22.45C-464.94, correlation coefficient R 2 =0.999; from Fig.14It can be seen that the regression equation corresponding to α-Fe2O3 is: S = 0.09C 2 -1.04C-141.02, correlation coefficient R 2 =0.998; from Fig.15 It can be seen that the regression equation corresponding to Fe3O4 is S = 0.04C 2 +1.79C-185.62, correlation coefficient R 2 =0.997; where S is the luminous intensity and C is the hydrogen sulfide concentration.
[0113] The γ-Fe2O3 prepared in Example 2 was used to detect three gas samples containing hydrogen sulfide, and the results measured by gas chromatography-mass spectrometry were taken as true values. The results are shown in Table 1.
[0114] Gas sample 1 is hydrogen sulfide, ethanol, trichloroethylene and dimethyl sulfide; gas sample 2 is hydrogen sulfide, trimethylamine and trichloroethylene; gas sample 3 is hydrogen sulfide and dimethylamine.
[0115] Table 1
[0116]
[0117] The degrees of freedom of the two sets of data for each sample are both 2. Look up the F value table, F 0.05,2,2 =19.00, F of the three samples <F 0.05,2,2 , indicating that there was no significant difference in the precision of the results obtained by the two methods.
[0118] f=n1+n2-2=4,P=95%,by looking up the table, t 0.05,4 =2.776; t <t 0.05,4 There was no significant difference between the results obtained by the two methods.
[0119] V GC-MS represents the parallel determination value of GC-MS method; V CTL Represents the CTL method replicate values.
[0120] A GC-MS represents the average value of the results of GC-MS method; A CTL Represents the average value of the results measured by CTL method.
[0121] The relative error is less than 2.5%, and the t test shows that, according to the table, t 0.05,4 =2.776, the test results of three samplings t <t 0.05,4 , indicating that there is no significant difference between the results obtained by the two methods.
[0122] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for detecting hydrogen sulfide, characterized in that: The steps include: The hydrogen sulfide gas reacts under the catalysis of the sensitive material, and the luminescent signal of the gas after the reaction is detected; the sensitive material includes at least one of Fe3O4, α-Fe2O3 and γ-Fe2O3; The preparation method of Fe3O4 comprises: reacting FeCl3·6H2O aqueous solution, FeCl2·4H2O aqueous solution and ammonia aqueous solution for 25 to 35 minutes, and then separating, washing and drying in sequence to obtain Fe3O4; The preparation method of α-Fe2O3 comprises: calcining the Fe3O4 at 300±5°C for 2.8 to 3.2 hours to obtain the α-Fe2O3; The preparation method of the γ-Fe2O3 comprises: calcining the Fe3O4 at 500±5°C for 2.8 to 3.2 hours to obtain the γ-Fe2O3.
2. The method for detecting hydrogen sulfide according to claim 1, characterized in that: The molar ratio of FeCl3·6H2O in the FeCl3·6H2O aqueous solution to FeCl2·4H2O in the FeCl2·4H2O aqueous solution is 1:(0.45-0.55).
3. The method for detecting hydrogen sulfide according to claim 2, characterized in that: The mass ratio of FeCl3·6H2O in the FeCl3·6H2O aqueous solution to NH3 in the ammonia aqueous solution is 10:(0.2-1).
4. The method for detecting hydrogen sulfide according to claim 2, characterized in that: The concentration of the FeCl3·6H2O aqueous solution is 0.08-0.12 mol / L.
5. The method for detecting hydrogen sulfide according to claim 2, characterized in that: The concentration of the FeCl2·4H2O aqueous solution is 0.045-0.055 mol / L.
6. The method for detecting hydrogen sulfide according to claim 3, characterized in that: The concentration of the ammonia solution is 4wt% to 6wt%.
7. The method for detecting hydrogen sulfide according to claim 3, characterized in that: The method comprises at least one of the following features (1) to (3); (1) The separation comprises magnetic decantation separation; (2) The washing comprises: washing with ethanol and deionized water; (3) The drying comprises: drying at 55 to 65° C. for 10 to 15 hours.
8. The method for detecting hydrogen sulfide according to claim 3, characterized in that: The detection wavelength of the luminescent signal is 300-555 nm.
9. The method for detecting hydrogen sulfide according to claim 8, characterized in that: The reaction temperature is 180-300°C.
10. The method for detecting hydrogen sulfide according to claim 9, characterized in that: The carrier gas includes air, and the flow rate of the carrier gas is 500 to 950 mL / min.
Citation Information
Patent Citations
Loaded nano-copper magnetic catalyst used for catalysis of solution of formaldehyde for preparing hydrogen and preparation method thereof
CN101862656A
Nanometer sensitive material for detecting hydrogen sulfide
CN102809557A
Preparation of p-n type nano CuO / alpha-Fe2O3 composite semiconductor material and application thereof as gas sensitive material
CN103257158A
Alpha-Fe2O3 nano microsphere hydrogen sulfide gas-sensing material and preparation of gas-sensing component
CN109133183A
Cataluminescence analysis method for detecting hydrogen sulfide based on nickel oxide
CN109187512A